2013
DOI: 10.1016/j.rmed.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of six minute walk test in cystic fibrosis adults

Abstract: The 6MWT provides prognostic information in CF adults, especially in subjects with FEV1 ≤ 60% predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
4
44
2
1
Order By: Relevance
“…In CF, absence of correlation between lung function and walking speed is keeping with previous findings 16, 30 even though Martin et al recently showed in a large observational study that low FEV1 was associated with a low distance in 6MWT in CF adult patients 23 . This discrepancy could be related to the difference in age and severity of CF patients between studies.…”
Section: Discussionsupporting
confidence: 87%
“…In CF, absence of correlation between lung function and walking speed is keeping with previous findings 16, 30 even though Martin et al recently showed in a large observational study that low FEV1 was associated with a low distance in 6MWT in CF adult patients 23 . This discrepancy could be related to the difference in age and severity of CF patients between studies.…”
Section: Discussionsupporting
confidence: 87%
“…Martin et al followed a cohort of adult patients with CF for 12 years, aiming to obtain prognostic data through the 6MWT. As a result, a 6MWD < 475m and FEV 1 ≤ 60% of what is expected were associated with pulmonary transplant or death 26 . Patients in this study who had a 6MWD< 500m showed higher oxygen desaturation.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is significant, as 6MW test performance has been correlated with risk of mortality in other vulnerable populations. 6MW distance less than 475 m was predictive of death or lung transplant in a cohort of adults with cystic fibrosis (48), and desaturation during the 6MW test was predictive of mortality among patients with idiopathic interstitial pneumonia (49).…”
Section: Discussionmentioning
confidence: 97%